1985
DOI: 10.1139/v85-493
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupolar relaxation effects in methyl-substituted ammonium ions as determined by 1H nuclear magnetic resonance

Abstract: . 63, 2975 (1985). Nitrogen-14 quadrupole interactions broaden the 'H nuclear magnetic resonances of the ammonium protons spin-coupled to 1 4~ in the methyl-substituted ammonium chlorides (methylammonium, dimethylammonium, and trimethylammonium). These proton lineshapes have been determined over the temperature range -8.3 to +93.6OC in 6 mol L-' aqueous HCl solution. The I4N spin-lifetimes, T , have been calculated from the Arrhenius form equation In T vs. I/T (K), and yield activation energies of 10.63 k 0.92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…During a recrystallization attempt of 3a , we isolated an unknown precipitate, whose 1 H NMR spectrum showed only this triplet at δ = 7.40 ppm (Figure S7). Further to this, the triplet exhibited a unique J -coupling constant of 50.9 Hz, which had been previously reported for the J 14 NH coupling of ammonium ions . We, therefore, hypothesized that this triplet was caused by ammonium chloride, which could be produced through spontaneous hydrolysis of the iminium group (see the outlined mechanism in Supporting Information; Figure S46).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…During a recrystallization attempt of 3a , we isolated an unknown precipitate, whose 1 H NMR spectrum showed only this triplet at δ = 7.40 ppm (Figure S7). Further to this, the triplet exhibited a unique J -coupling constant of 50.9 Hz, which had been previously reported for the J 14 NH coupling of ammonium ions . We, therefore, hypothesized that this triplet was caused by ammonium chloride, which could be produced through spontaneous hydrolysis of the iminium group (see the outlined mechanism in Supporting Information; Figure S46).…”
Section: Resultssupporting
confidence: 68%
“…Further to this, the triplet exhibited a unique J-coupling constant of 50.9 Hz, which had been previously reported for the J 14 NH coupling of ammonium ions. 45 We, therefore, hypothesized that this triplet was caused by ammonium chloride, which could be produced through spontaneous hydrolysis of the iminium group (see the outlined mechanism in Supporting Information; Figure S46). Such hydrolysis reactions had been previously observed for imidates and amidines, too.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The quadrupole relaxation of 14 N nucleus can have effects on the nearby magnetic nuclei since rapid quadrupole relaxation can broaden J -coupling between the two nuclei and lead to line broadening. It has been reported that the quadrupole relaxation of 14 N became faster at lower temperature for the ammonium ions, therefore leading to the line broadening . Such broadening is related to the distance between the two nuclei.…”
Section: Resultsmentioning
confidence: 95%
“…Its 1 H NMR spectrum showed only this triplet at δ = 7.40 ppm with a unique J-coupling constant of 50.9 Hz (Figure S7), the latter which had been previously reported for J14 NH coupling of ammonium ions. 56 We therefore hypothesized that the iminium group can undergo spontaneous hydrolysis to release ammonium chloride (see outlined mechanism in the ESI, Figure S44); this had been previously observed for imidates and amidines, too. 57,58 Through a comparison between FT-IR spectra of this unknown precipitate and commercially available ammonium chloride, our supposition was con-firmed as both spectra were identical (Figure S8).…”
Section: Synthesis Of γ-Functional Itl Derivativesmentioning
confidence: 78%